Computational advances in the design and discovery of artemis inhibitors for radiosensitization in cancer therapy - Maryam Bashir; Usman Abdullah; Sadia Nazir; Farhan Siddique; Nasir Jalal (Frontiers in Chemistry)
IntroductionArtemis is a key scaffold repair protein involved in the non-homologous end-joining (NHEJ) DNA repair pathway and is encoded by the DCLRE1C gene in humans. Its inhibition disrupts double-strand break (DSB) repair, sensitizing cancer cells to ionizing radiation (IR). However, no Artemis-targeted inhibitors are currently available for therapeutic use. This study aims to identify and characterize novel small-molecule Artemis inhibitors that act as potential radiosensitizers in cancer treatment.MethodsMicronuclei formation was assessed in Artemis-deficient (CJ179), proficient (1BR3), and mutant (48BR) cell lines following 1 Gy IR exposure. Initial in vitro screening identified HMAD as a potential Artemis inhibitor. A focused virtual screening of 69 compounds was performed using AutoDock4 and Glide to evaluate binding affinity to Artemis. The top 16 compounds (ΔG < −8.0 kcal/mol) were further analyzed. Density Functional Theory (DFT) calculations at the B3LYP/6−311+G(d,p) level were used to assess frontier molecular orbitals and reactivity. ADMET profiling was conducted to evaluate pharmacokinetic properties. Compounds 42 and 51 were subjected to 100 ns molecular dynamics (MD) simulations with MMGBSA binding free energy calculations, PCA, and FEL analysis.ResultsCJ179 cells exhibited significantly higher micronuclei post-irradiation, confirming Artemis’s role in DNA repair. Among the top hits, compound 42 showed a highly stable binding profile, with a favorable MMGBSA binding energy of −36.94 kcal/mol. ADMET analysis indicated optimal drug-like properties. MD simulations revealed stable interaction trajectories, hydrogen bonding, and a narrow binding pocket. PCA and FEL analysis further supported the dynamic stability of compound 42.DiscussionThis study identifies compound 42 as a promising Artemis inhibitor with potential as a radiosensitizing agent. The integrated in vitro and computational findings offer a foundation for further preclinical development, contributing to more effective radiotherapy strategies in cancer treatment.